2010
DOI: 10.1159/000320108
|View full text |Cite
|
Sign up to set email alerts
|

Is Transition Zone Sampling at Repeated Saturation Prostate Biopsy Still Useful

Abstract: Objectives: To evaluate retrospectively the detection rate of prostate cancer (PCa) located only in the transition zone (TZ) by directed cores at repeated saturation prostate biopsy (SPB). Methods: From July 2001 to December 2009, 380 and 43 patients (median age: 63 years) underwent second and third SPB because they were persistently suspicious for PCa. Indications for biopsy were: prostate-specific antigen (PSA) of >10 ng/ml, and PSA between 4.1 and 10 ng/ml or 2.6 and 4 ng/ml with free/total PSA of ≤25 and ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Meanwhile, the sample from the prostatic transition zone by directed needle biopsies may be omitted due to a lower detection rate compared to TURP. 97,98 Initial therapy in primary localized PCa Initial therapy in primary localized PCa includes radical prostatectomy (RP), hormone therapy (HT), brachytherapy and external-beam radiation therapy (RT).…”
Section: Prostate Cancer (Pca) Epidemiological Characteristicsmentioning
confidence: 99%
“…Meanwhile, the sample from the prostatic transition zone by directed needle biopsies may be omitted due to a lower detection rate compared to TURP. 97,98 Initial therapy in primary localized PCa Initial therapy in primary localized PCa includes radical prostatectomy (RP), hormone therapy (HT), brachytherapy and external-beam radiation therapy (RT).…”
Section: Prostate Cancer (Pca) Epidemiological Characteristicsmentioning
confidence: 99%
“…There has been no general agreement regarding the number of cores and the optimal approach. In addition, we noticed that there was no specific relationship between the method used and the cancer detection rates (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) (Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that even low-risk PCA may demonstrate disease upgrading or upstaging. 5 , 6 Even known indicators of the severity of PCA, such as prostate-specific antigen (PSA) kinetics or initial biopsy results at the time of PCA diagnosis, do not reliably predict adverse pathology when men are monitored by AS. 7 Therefore, imaging techniques have played an increasingly important role in the management of localized PCA.…”
Section: Introductionmentioning
confidence: 99%